2007
DOI: 10.1152/japplphysiol.01334.2006
|View full text |Cite
|
Sign up to set email alerts
|

WISE 2005: stroke volume changes contribute to the pressor response during ischemic handgrip exercise in women

Abstract: The mechanism of the pressor response to small muscle mass (e.g., forearm) exercise and during metaboreflex activation may include elevations in cardiac output (Q) or total peripheral resistance (TPR). Increases in Q must be supported by reductions in visceral venous volume to sustain venous return as heart rate (HR) increases. Therefore, this study tested the hypothesis that increases in Q, supported by reductions in splanchnic volume (portal vein constriction), explain the pressor response during handgrip ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
82
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 36 publications
12
82
6
Order By: Relevance
“…For correlations between ⌬LVR and ⌬MAP, ⌬CO, or ⌬TPR from the rest period to the exercise period, n ϭ 31 subjects; for all other correlations, n ϭ 35 subjects. *P Ͻ 0.05; †P Ͻ 0.01. ric exercise, as was suggested by measurements of renal and splanchnic vascular resistance and blood flow in both animals (8,12,63) and humans (39,42,(57)(58)(59)64). This might explain our observation that individual differences in LVR and CO responses were dissociated during exercise, despite a strong relationship between TPR and CO responses.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…For correlations between ⌬LVR and ⌬MAP, ⌬CO, or ⌬TPR from the rest period to the exercise period, n ϭ 31 subjects; for all other correlations, n ϭ 35 subjects. *P Ͻ 0.05; †P Ͻ 0.01. ric exercise, as was suggested by measurements of renal and splanchnic vascular resistance and blood flow in both animals (8,12,63) and humans (39,42,(57)(58)(59)64). This might explain our observation that individual differences in LVR and CO responses were dissociated during exercise, despite a strong relationship between TPR and CO responses.…”
Section: Discussionsupporting
confidence: 66%
“…While the increase in arterial pressure during isometric exercise is a well-established response, the responses of the components mediating the pressor response, cardiac output (CO) and total peripheral vascular resistance (TPR), remain controversial. In fact, previous studies have shown that, during isometric handgrip exercise in healthy humans, the pressor response occurs via an increase in CO (16,32,[34][35][36]57), an increase in TPR (6, 17), or both of those (3,31,58,59,61,62). The variability of those findings leads one to speculate that there are considerable individual differences in the components of the pressor response to exercise, which is in stark contrast to the nearly invariant arterial pressure response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MEAN BLOOD PRESSURE RESPONSE (MBP) to metaboreflex activation in healthy individuals is normally the consequence of increases in both systemic vascular resistance (SVR) and cardiac output (CO) (3,9,10,12,14,24,29,31,54,56). This response is achieved as the result of an elevation in sympathetic tone, which produces arteriolar constriction and enhancement in myocardial performance and in cardiac preload (18,35,39).…”
Section: The Main New Finding Of the Present Investigation Is That Obmentioning
confidence: 99%
“…Third, with respect to the limitations of the model used to evoke the metaboreflex, both static and dynamic contractions followed by local circulatory occlusion increase HR, SV, and CO in humans (3,24,32) and in dogs (29), but the effects on the heart appear to be intensity-dependent (7,8,40). However, the local circulatory occlusion used to trap metabolites that activate metaboreflex prevents venous dilation, which is a major component of metaboreflex activation (10,25).…”
Section: Limitationsmentioning
confidence: 99%